Mitochondrial remodeling underlying age-induced skeletal muscle wasting: let's talk about sex - Moreira-Pais, Alexandra; Vitorino, Rui; Sousa-Mendes, Cláudia; Neuparth, Maria João; Nuccio, Alessandro; Luparello, Claudio; Attanzio, Alessandro; Novák, Petr; Loginov, Dmitry; Nogueira-Ferreira, Rita; Leite-Moreira, Adelino; Oliveira, Paula A; et al. (Free radical biology & medicine, 2024)
Sarcopenia is associated with reduced quality of life and premature mortality. The sex disparities in the processes underlying sarcopenia pathogenesis, which include mitochondrial dysfunction, are ill-understood and can be decisive for the optimization of sarcopenia-related interventions. To improve the knowledge regarding the sex differences in skeletal muscle aging, the gastrocnemius muscle of young and old female and male rats was analyzed with a focus on mitochondrial remodeling through the proteome profiling of mitochondria-enriched fractions. To the best of our knowledge, this is the first study analyzing sex differences in skeletal muscle mitochondrial proteome remodeling. Data demonstrated that age induced skeletal muscle atrophy and fibrosis in both sexes. In females, however, this adverse skeletal muscle remodeling was more accentuated than in males and might be attributed to an age-related reduction of 17beta-estradiol signaling through its estrogen receptor alpha located in mitochondria. The females-specific mitochondrial remodeling encompassed increased abundance of proteins involved in fatty acid oxidation, decreased abundance of the complexes subunits, and enhanced proneness to oxidative posttranslational modifications. This conceivable accretion of damaged mitochondria in old females might be ascribed to low levels of Parkin, a key mediator of mitophagy. Despite skeletal muscle atrophy and fibrosis, males maintained their testosterone levels throughout aging, as well as their androgen receptor content, and the age-induced mitochondrial remodeling was limited to increased abundance of pyruvate dehydrogenase E1 component subunit beta and electron transfer flavoprotein subunit beta. Herein, for the first time, it was demonstrated that age affects more severely the skeletal muscle mitochondrial proteome of females, reinforcing the necessity of sex-personalized approaches towards sarcopenia management, and the inevitability of the assessment of mitochondrion-related therapeutics.
Keywords: Rats; Aging; Fibrosis; mitochondrie; Oxidative phosphorylation; Mitochondria, Muscle; mitofagie; sexuální faktory; Muscular Atrophy; mužské pohlaví; Muscle, Skeletal; ubikvitinligasy; Sarcopenia; krysa rodu Rattus; svalová atrofie; stárnutí; Ubiquitin-Protein Ligases; ženské pohlaví; Proteome; zvířata; svalové mitochondrie; kosterní svaly; Sex Factors; Estradiol; Mitophagy; Mitochondria; sarkopenie; Sexual dimorphism; fibróza; proteom; Fatty acid oxidation; Female; estradiol; Male; Animals